Primary Sources and Asian Pasts - Bisschop, Peter C.; Cecil, Elizabeth A. (Beyond Boundaries, 2020)
This conference volume unites a wide range of scholars from diverse fields in an effort to explore new perspectives and methods in the study of primary sources from the premodern world. It represents the culmination of the ERC's Synergy project Asia Beyond Boundaries, a research consortium of the British Museum, the British Library and the School of Oriental and African Studies, in partnership with Leiden University.